Avaliação da condição periodontal em indivíduos portadores de miastenia gravis - Rafael Jordão Storino Vaz Monteiro (2016)
Myasthenia gravis is an autoimmune neuromuscular disorder characterized by peripheral fatigue and weakness, caused by damage caused by antibodies directed against the acetylcholine receptor at the neuromuscular junction. Periodontitis is an inflammatory chronic infectious disease that leads to destruction of tissue supporting the teeth, characterized by the presence of elevated concentrations of inflammatory mediators in the gingival fluid, and the host response plays an important role in their pathogenesis. There is evidence of the association between autoimmune diseases and periodontitis. The aim of this study was to evaluate the periodontal clinical parameters and self-reported measures in individuals with myasthenia gravis (MG). A cross-sectional study was conducted with patients of the Ambulatório de Doenças Neuromusculares do Serviço de Neurologia do Hospital das Clínicas da Universidade Federal de Minas Gerais. The sample consisted of 36 patients with MG. Medical and sociodemographic data of interest were collected. Patients underwent a periodontal examination of the entire mouth and answered a questionnaire of self-reported periodontal measures. From the 36 subjects, 29 (80.6%) were women and 7 (19.4%) were men with a mean age of 38.7 ± 15.6 years. 41.6% of participants had MGFA rating equal to V, 30.6% of the sample had up to 5 years of disease, and 44.5% had 1 to 5 points of MG composite. Individuals with longer MG ( 21 years) had a higher percentage of sites with NIC 3 to 4 mm, 5 to 6mm and 7mm. Variables associated with the % of sites with NIC 3 to 4mm were the time of MG (p = 0.038), and smoking (p = 0.010). Variables associated with the % sites with NIC 5 to 6mm were age (p = 0.035), time of MG (p = 0.008) and smoking status (p = 0.002). The prevalence of periodontitis in the sample was 52.7% (n = 19). Periodontitis cases were older (p = 0.002) and presented longer MG (p = 0.007). No-cases of periodontitis presented a higher frequency of corticosteroid use (p = 0.048). In relation to self-reported periodontal measures, sensitivity ranged from 5.3% to 64.7%, and specificity ranged from 17.6% to 100.0%. Variables associated with periodontitis were age [OR = 35.6 (95% CI 3.61 to 351.52); p = 0.020] and corticosteroid use [OR = 0.09 (95% CI 0.01 to 0.92); p = 0.042). It was concluded that the time of myasthenia gravis affects periodontal condition and that the use of corticosteroids was considered a protective factor.